Implementation Of Workplace Safety Standards In The Culinary Industry: A Case Study Of Soto XYZ - Desmantyo, Pandu Sapto; Rifai, Muhammad Syakib Asqalani (International Journal of Economics Development Research (IJEDR), 2024)
The study focuses on the implementation of work safety standards within the culinary industry, utilizing the Soto XYZ restaurant in Bandung as a case study. Given the high potential for accidents and health issues in restaurant and kitchen settings, this research aims to assess the compliance and effectiveness of current safety standards, as well as to identify potential risks. Initial findings highlight a general lack of attention to occupational safety within the culinary sector, including at Soto XYZ, where safety training and the use of personal protective equipment are notably inadequate. It is evident that the current implementation of safety standards at Soto XYZ is suboptimal, as reflected by insufficient safety training, limited use of protective equipment, and low awareness of safety protocols. However, the study also reveals a positive link between adherence to safety standards and improved productivity and employee well-being. Strategic recommendations for enhancing safety practices include regular training, provision of adequate safety equipment, and efforts to raise safety awareness among staff. Furthermore, the involvement of partners in providing resources and support to establish better safety standards within the culinary industry is deemed crucial. It is anticipated that the implementation of these suggestions will result in a safer and more positive working environment.